2011
DOI: 10.1002/cae.20557
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the accessibility of three open‐source learning content management systems: A comparative study

Abstract: Learning content management systems (LCMSs) have become increasingly popular in the educational field over the past few years. However, problems in system design can create difficulties in the interactions between LCMSs and an important sector of the user population. The assessment and monitoring of LCMS accessibility are vital for the guarantee of universal accessibility in education. This article presents a comparative study of the accessibility of three web-based, open-source LCMSs: Moodle, ATutor, and Saka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 8 publications
0
17
0
3
Order By: Relevance
“…The Moodle 1 LCMS was selected for evaluation in this study in light of two principal considerations, namely, the fewer accessibility-related barriers identified in prior studies relative to other LCMSs, as well as the former's status as the most commonly-used and recommended LCMS around the world [6]. This paper presents user and heuristic evaluations of Moodle's accessibility for screen reader users attempting to create and manage a course on the platform [7].…”
Section: Introductionmentioning
confidence: 99%
“…The Moodle 1 LCMS was selected for evaluation in this study in light of two principal considerations, namely, the fewer accessibility-related barriers identified in prior studies relative to other LCMSs, as well as the former's status as the most commonly-used and recommended LCMS around the world [6]. This paper presents user and heuristic evaluations of Moodle's accessibility for screen reader users attempting to create and manage a course on the platform [7].…”
Section: Introductionmentioning
confidence: 99%
“…European Unified Framework for Accessible Lifelong Learning (EU4ALL) was a major collaborative project [8], which highlighted the importance of adapting online learning resources for all, and stressed the need to make accessible content available. Problems regarding access to LMS (Learning Management Systems) from the registration or login process and difficulties for user interaction with learning resources such as forums and documents have been reported [9,10]. While conducting the literature review we have observed that there has been limited research focused on the accessibility of MOOCs.…”
Section: State Of the Art: Accessibility And Moocsmentioning
confidence: 99%
“…Therefore, a number of webbased open-source LCMSs have been explored by researchers. One of these studies was conducted by Iglesias et al [23] to evaluate three web-based open-source LCMSs (ATutor 1.6.2, Moodle 1.9.4, and Sakai 2.6.0). This type of study requires an assessment and monitoring of LCMS accessibility to guarantee the universal accessibility of this type of systems.…”
Section: Related Workmentioning
confidence: 99%